Posodabljanje prevodov - Kaloh Vid, Natalia (Slavistična revija, 2017)
F. M. Dostojevsky's novel The Brothers Karamazov has been translated into Slovenian twice. Vladimir Levstik's translation was published in 1929 and Borut Krashevec's re-translation in 2010. The current analysis is part of a discussion on the effect of re-translations from the perspective of using domesticating and foreignizing strategies when rendering culturally specific items. The analysis seeks to evaluate the "Re-translation Hypothesis," which interprets each subsequent translation as an attempt to "improve" the previous, defining "improvement" by merely one criterion"i. e., keeping as many foreign elements in the translation as possible. We analyzed both translations on the micro-linguistic level and focused on the issue of equivalence when translating culturally specific terms.
Keywords: "Brat'ja Karamazovy"; Dostoevskij, Fedor Mihajlovič, 1821-1881; multikulturnost; prevajanje; ruski roman; translation